Sensitivity methods in control theory : proceedings of an International Symposium held at Dubrovnik, August 31-September 5, 1964 - Radanovic, L. (Symposium Publications Division, Pergamon Press, 1966)
Sensitivity Methods in Control Theory is a collection of manuscripts presented as the Third International Symposium of Sensitivity Analysis, held at Dubrovnik, Yugoslavia on August 31-September 5, 1964, sponsored by The Theory Committee of International Federation of Automatic Control. Sensitivity theory or sensitivity analysis concerns the solution of problems associated with parameter variations within the general scope of control theory.